CASE STUDY ANALYSIS OF THE CROSS CULTURE RESEARCH : CASE STUDY ANALYSIS OF THE CROSS CULTURE RESEARCH - I Gede Nika Wirawan (Universitas Bali Dwipa, 2022)
The analysis is based on three hypotheses which is not correlated one other. There are three hypothesis used in this research. The first one is the economic explanation, the second one is cultural values, and the last one is cognitive explanation. The first hypothesis (economic explanation) is not reliable if we combine to the third hypothesis (cognitive explanation) because those theories overlap each other. Theory of economic explanation mentions that there is a positive relationship between the economic health of cities and helping people. It means that the healthier of the economic condition in one city would affect the positively in the behavior of the people in helping the other people. So, we would expect that the rich city which has an excellent economic condition would have a tendency in helping the others. Meanwhile the theory of cognitive explanation mentions that the people in the country which have a high walking speed would tend not to help the others since everybody is busy with their own business and have a lack of time to help the people in the street.